The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1159/000069463
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A Radiation (320–400 nm) Protects Hairless Mice from Immunosuppression Induced by Ultraviolet B Radiation (280–320 nm) or <i>Cis-</i>Urocanic Acid

Abstract: T cell-mediated immune function, here measured as the contact hypersensitivity reaction, is readily suppressed by moderate exposure of mice to ultraviolet B (UVB) or solar-simulated radiation (SSUV), or by topical application of cis-urocanic acid. The effect of ultraviolet A (UVA) radiation on immune function has been unclear. Here we have demonstrated that when UVA radiation from a fluorescent tube source was rigorously filtered to remove contaminating UVB radiation, it was immunologically innocuous at phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 20 publications
(34 reference statements)
12
89
1
Order By: Relevance
“…We have speculated that the mechanism of UVA photoimmunoprotection involves a UVA photoproduct that is relatively stable and persists for at least 24 h in the cutaneous environment, perhaps localized in the dermis where it would be preferentially produced by UVA rather than UVB radiation (10). This study has tested the hypothesis that induced HO-1 acts in this role and has shown that, whereas there is measurable HO enzyme activity present constitutively in hairless mouse skin, cutaneous HO activity is also UVA inducible and remains elevated for a period of at least 3 d after UVA irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have speculated that the mechanism of UVA photoimmunoprotection involves a UVA photoproduct that is relatively stable and persists for at least 24 h in the cutaneous environment, perhaps localized in the dermis where it would be preferentially produced by UVA rather than UVB radiation (10). This study has tested the hypothesis that induced HO-1 acts in this role and has shown that, whereas there is measurable HO enzyme activity present constitutively in hairless mouse skin, cutaneous HO activity is also UVA inducible and remains elevated for a period of at least 3 d after UVA irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure to such UVA radiation induced a state of resistance in the mice to the immunosuppressive effects of either UVB radiation or cis-UCA (10), both of which could be applied before, immediately after, or up to 24 h after the UVA radiation. We postulated that UVA exposure may induce a relatively long-lived, but as-yet-unidentified, immunoprotective photoproduct that can inhibit the activity of cis-UCA and thus provide protection from UVB-induced photoimmunosuppression.…”
mentioning
confidence: 99%
“…We have found in mice that UVA irradiation protects from UVB-induced immunosuppression. 1 We observed different cytokine modulation in mouse epidermis by the UVA and UVB wavebands: UVA acts as an inducer of Th1-derived cytokines like IL-12 and IFN-γ, while UVB is responsible for induction of Th2-derived cytokines like IL-10, a major cause of immunosuppression. 2 However, the underlying mechanism(s) by which UVA achieved immunoprotection against UVB have remained undefined.…”
Section: Introductionmentioning
confidence: 83%
“…1 Mouse skins were fixed, processed and paraffin embedded immediately and at 24 hourly intervals for 5 days post-irradiation. FasL antibody was used to detect FasL expression in mouse skin by immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…They indicated that the mechanism of UVA immunoprotection involves the induction of cutaneous HO-1 (37,38). Moreover, they reported that UVA irradiation upregulated HO-1 in the dermis and epidermis of hairless mouse skin, and UVA-induced HO enzyme activity is protective against UVB-induced immunosuppression (10,39).…”
Section: Ho-1 In Uva-induced Immunoprotectionmentioning
confidence: 99%